Symptom Experiences and Coping Strategies among Multi-ethnic Solid Tumor Patients Undergoing Chemotherapy in Malaysia - Yahaya, N.A.; Subramanian, P.; Bustam, A.Z.; Mohd Taib, N.A. (Asian Pacific Organization for Cancer Prevention, 2015)
Background: This study was performed to assess patient symptoms prevalence, frequency and severity, as well as distress and coping strategies used, and to identify the relationships between coping strategies and psychological and physical symptoms distress and demographic data of cancer patients. This cross-sectional descriptive study involved a total of 268 cancer patients with various types of cancer and chemotherapy identified in the oncology unit of an urban tertiary hospital. Materials and Methods: Data were collected using questionnaires (demographic questionnaire, Medical characteristics, Memorial Symptom Assessment Scale (MSAS) and Brief COPE scales and analyzed for demographic, and disease-related variable effects on symptom prevalence, severity, distress and coping strategies. Results: Symptom prevalence was relatively high and ranged from 14.9% for swelling of arms and legs to 88.1% for lack of energy. This latter was the highest rated symptom in the study. The level of distress was found to be low in three domains. Problem-focused coping strategies were found to be more commonly employed compared to emotion-focused strategies, demonstrating significant associations with sex, age group, educational levels and race. However, there was a positive correlation between emotion-focused strategies and physical and psychological distress, indicating that patients would choose emotion-focused strategies when symptom distress increased. Conclusions: These findings demonstrate that high symptom prevalence rates and coping strategies used render an improvement in current nursing management. Therefore development of symptoms management groups, encouraging the use of self-care diaries and enhancing the quality of psychooncology services provided are to be recommended.